2022
DOI: 10.3389/fgene.2022.973585
|View full text |Cite
|
Sign up to set email alerts
|

A review on the importance of miRNA-135 in human diseases

Abstract: MicroRNA-135 (miR-135) is a microRNA which is involved in the pathoetiology of several neoplastic and non-neoplastic conditions. Both tumor suppressor and oncogenic roles have been reported for this miRNA. Studies in prostate, renal, gallbladder and nasopharyngeal cancers as well as glioma have shown down-regulation of miR-135 in cancerous tissues compared with controls. These studies have also shown the impact of miR-135 down-regulation on enhancement of cell proliferation and aggressive behavior. Meanwhile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 120 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…In a recent publication in E. sea bass, the authors identified higher levels of circulating miR-499 in plasma differentiating males when comparted to differentiating females (Houdelet et al, 2023). Another example of a male-like miRNAs in fish gonads is the miR-135, which is a biomedical marker in humans due to its involvement in many cancer and disorders like Alzheimer disease (Kadkhoda et al, 2022; Zheng et al, 2021). Similar to our data, in tilapia, miR-135 presented sexual dimorphism towards males as it was upregulated in testes together with miR-33a, miR-132 and miR-212 (Herkenhoff et al, 2018; Xiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication in E. sea bass, the authors identified higher levels of circulating miR-499 in plasma differentiating males when comparted to differentiating females (Houdelet et al, 2023). Another example of a male-like miRNAs in fish gonads is the miR-135, which is a biomedical marker in humans due to its involvement in many cancer and disorders like Alzheimer disease (Kadkhoda et al, 2022; Zheng et al, 2021). Similar to our data, in tilapia, miR-135 presented sexual dimorphism towards males as it was upregulated in testes together with miR-33a, miR-132 and miR-212 (Herkenhoff et al, 2018; Xiao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although this is among the first studies to report this finding, two other recent studies have found expression of miR-135 may be associated with partial differentiation in DPSC, which may explain why this is found among the slower-growing and potentially partially differentiated DPSC isolates (Ghahfarrokhi et al, 2020;Li et al, 2015). Interestingly, most other studies of miR-135 have demonstrated associations with specific types cancer-including digestive system cancers, which may also suggest that some tissue-specific differentiation may influence the expression of this microRNA that is restricted to specific types of cells and tissues in very specific locations (Kadkhoda et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 125 miR-135 Targets AKT and Wnt signaling pathways, and APC, FOXO1, FOXN1, RECK, some matrix metalloproteinases gene expression. 126 miR-144 Modulates the Src/AKT/ERK, Notch, JAK2/STAT3, EGFR, and PTEN/PI3K/AKT signaling pathways. 127 miR-153 Reduces PTEN expression.…”
Section: Are Mirnas Involved In the Pathogenesis Of Diabetes Mellitus...mentioning
confidence: 99%
“… 125 hsa-miR-135 Increased 66 Reduced in prostate, renal, gallbladder, and nasopharyngeal cancers, as well as in glioma, impacting the enhancement of cell proliferation and aggressive behavior. 126 Increased in bladder, oral, colorectal, and liver cancers. 126 Dual role in in breast, gastric, lung, and pancreatic cancers, as well as in head and neck squamous cell carcinomas.…”
Section: Are Mirnas Involved In the Pathogenesis Of Diabetes Mellitus...mentioning
confidence: 99%